Cover Image, Volume 138, Issue 45. Issue 45 (24th August 2021) - Lyu, Lingyun; Hanada, Takeshi; Yamahira, Naohiro; Morita, Jun; Yamamoto, Ryota; Itomi, Ken; Adachi, Takumi; Kubouchi, Sho; Horiuchi, Shin
Abstract : The cover image by Shin Horiuchi and co‐authors shows how the distribution of nano‐sized silica in binary rubber blends is characterized by scanning transmission electron microscopy (STEM) tomography, combined with energy dispersive X‐ray spectrometry (EDX). 3D distribution of silica, is visualized by STEM‐EDX tomography. The phase‐separated morphologies of polyisoprene rubber (IR) and styrene‐butadiene rubber (SBR) meanwhile is visualized by STEM‐tomography in high‐angleannular‐dark field (HAADF) mode. The combination of STEM‐EDX and STEM‐HAADF tomography determines the distribution of silica between the two rubber phases quantitatively. The silica in IR (light blue) and in SBR (dark blue) phases can be identified as yellow and pink regions, respectively. DOI: 10.1002/app.51443